ضوابط المصلحة في قضايا المعاملات المالية المعاصرة بيع السلم والاستصناع نموذجا /‏ - عبد العزيز، سمية (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study attempts to highlight several fundamental issues on the limitations of maslaÍah in the application of Salam and Istisna' contracts in Islamic banking and finance transactions. Various applications and products of Islamic transaction offered in Malaysia have made Malaysia as one of the leading Islamic banking and finance institutions in the world. However, this positive development has raised several concerns on the legitimacy of modern financial transactions in adhering to the true guidelines of the Islamic law of transactions. The findings of this study suggest several solutions to the limitation in the applications of maslaÍah in Islamic transaction involving Salam and Istisna' contracts which fulfill the objectives of the shari'ah in hifz al-mal. Therefore, the role of a Shari'ah Advisory Council in advising every Islamic financial institution to comply with the rulings of shariah is important for these institutions to grow to greater heights. This study attempts to suggest a few important guidelines or restrictions on the application of maslahah on modern financial transactions, particularly application of Salam and Istisna'.